Wishing to be the Animal in Kurdish Poem in General and “Qubad Jalil Zada’poem if we were Dog - Aziz, Bestoon Arif; Hussain, Atta Rashid (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
This paper is an attempt to analyze the subject of wishing to be the animal in Kurdish poem in general and “Qubad Jalil Zada’poem if we were dog” in particular. for this reason, we divided this study into some parts. First we discuss about the subject of animalization according to philosophical and literary perspective. Then we talked about it in Kurdish poem in general and we studied some the works of some Kurdish poets. We focused on “Qubad Jalil Zada’poem if we were dog” and analyzed the reasons which led him to believe that the life of animal is better than the life of humanbeings. This idea come from the deep awareness and experience of the poet which he has about the life of people, despite the ending of the human’ value such as liberty, religion, culture, politics, nature and technology. The importance of this study is that we explain the phenomenon in classical and modern Kurdish poetry, and we compare the reason of this phenomenon in both periods. In conclusion we talked about some points we reached throughout this study and writing the references according to Harvard system which is the newest system.